2021
DOI: 10.3390/healthcare9101320
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for a Systematic Review and Meta-Analysis of Mind–Body Modalities to Manage the Mental Health of Healthcare Workers during the COVID-19 Era

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become an unprecedented threat to humanity worldwide, including healthcare workers (HCWs). Mind–body modalities have been used to improve the mental health, well-being, quality of life, and physical health of clinical and general populations, and may also be used to improve the mental health of HCWs during COVID-19. The objective of this review is to analyze the effectiveness of mind–body modalities for the mental health of HCWs in the COVID-19 era. Six elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Inquiry-based stress reduction (IBSR) has been shown to effectively improve teachers' well-being, resilience, and burnout [41]. However, its usefulness for healthcare workers during the COVID-19 pandemic should be examined [42].…”
Section: Discussionmentioning
confidence: 99%
“…Inquiry-based stress reduction (IBSR) has been shown to effectively improve teachers' well-being, resilience, and burnout [41]. However, its usefulness for healthcare workers during the COVID-19 pandemic should be examined [42].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of this systematic review was published as a paper [ 17 ] and registered in the Open Science Framework registry ( , accessed on 13 August 2021). This systematic review complies with Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 statement ( Supplementary Material File S1 ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, even though previous research has demonstrated that individuals with high levels of trait mindfulness have better responsiveness to emotional stress and better recovery from negative emotions ( Fogarty et al, 2013 ), current research has focused on providing evidence of the effectiveness of mindfulness-based interventions ( Kwon and Lee, 2021 ), few studies have systematically examined the impact of mindfulness as a potential protective factor for the public mental health in response to the COVID-19 pandemic. Therefore, to provide a clearer reference for the public and the government in their response to the COVID-19 epidemic, it is essential to properly review and assess these research results.…”
Section: Introductionmentioning
confidence: 99%